(3eWGdH GdCPcjGA hChdj GdCdHGHs - (3GdYTGbj, Ydj Hf YHO Gddg, J b (B12 (3g`s ((3ESeGYjd Hf chdjs)
(3ChdgG (B:s
(3GdMeO def dG jONd fYeg GdeJVGYaI aj GdMSGH agPg QSGdI aj GdMSGH QbeJgG GSJLdGHG dOYGA GdWdGH hWdHG dQVGA QH GdCQHGH hQJHJgG Ydi SJI eWGdH GdeWdH GdChd aj GdLeY hgh RjGOI YOO Ydi BNQ s
(3BNQgG (B:s
(3hGNJjGQ UMI GdJbSje eWdbG HVQH ejRGf aj ejRGf Gdebhe Ydjg hRjGOI ejRGf Ef hLO Ydi GdMGUd aefg Cf GdeLJeY dEPG NGda GdebShe aGdYed NWC hEdG aUhGH Jes
(3JHUQI GdYfhGf (B:s
(3aj GdMSGHs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdQjGVjGJs